Dažas valodas īpatnības senākā posma latgaliešu rakstu avotos - Stafecka, Anna (Baltistica, 1998)
LINGUISTIC PECULIARITIES OF THE LATGALIAN WRITTEN MONUMENTS In this article the author deals with the linguistic peculiarities reflected in the Latgalian written sources of the 18th and early 19th centuries. The main attention is paid to the morphological forms in five books. The similarity of some texts is also noticed. More related are the both Catechisms, some similarity is observed in the Catechism of 1775 and in the translation of Gospels of 1753. More distinctive is the book of 1805 “Wyʃʃa Mocieyba Katoliszka”.